Monitoring of Policy Implementation: Convergent Mobile and Fixed Technologies as Emergent Enablers - Adham K.A.; Sarkam S.F.; Said M.F.; Nasir N.M.; Kasimin H. (Springer New York LLC, 2024)
Indexed by SCOPUS